PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X DAN XI IPS DI SMAN 1 TAMBUSAI UTARA KABUPATEN ROKAN HULU - Siagian, Muliani; ', Sumarno; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was conducted at SMAN 1 North Tambusai Rokan Hulu Regency with the aim to analyze the influence of learning motivation on student learning outcomes.The population in this study were 134 students of class X and XI IPS and the sample in this study were 57 respondents using Simple Random Sampling technique based on the Slovin formula. Data collection techniques were conducted through the provision of questionnaires and documentation.Data were analyzed using simple regression analysis.The results showed that the variable of motivation have an effect on student learning result variable.Furthermore, motivation variable influence student learning outcomes of 6,218 with coefficient of determination equal to 81,8%. Suggestions relating to the results of research that is to improve learning outcomes, student teachers should be able to motivate students by providing tasks that are not routine that are independent and not boring.Keywords: Learning Motivation, Learning Outcomes